(untitled) (World Economics and Finance Bulletin, 2024)
The article examines theoretical and practical issues related to econometric modeling of the innovative development of the regions of the Republic of Uzbekistan. In particular, the influence of the innovative state of the regions on the country’s economy is high, and the interdependence of these indicators has been shown with the help of an econometric model, and some recommendations have been developed in this regard